2003
DOI: 10.5688/aj6704109
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and Novel Predictors of Classroom and Clerkship Success of Pharmacy Students

Abstract: Objectives. This study was designed to assess the extent to which 7 traditional and novel predictors contribute to overall pharmacy grade point average (pharmacy GPA), first through third year pharmacy GPA (1-3 year GPA), and clerkship GPA of pharmacy students. Methods. This investigation used a convenience sample and a blinded retrospective record review of the first 3 class years of Doctor of Pharmacy students at Shenandoah University's Bernard J. Dunn School of Pharmacy (Classes of 2000, 2001, and 2002). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 21 publications
2
63
1
3
Order By: Relevance
“…In their study conducted at a 4-year pharmacy program, Kidd and Latif found that PCAT composite score did not predict fourth-year experiential performance. 4 Our results suggest that additional admissions measures for experiential success are needed in order to ensure the students' overall academic success. In a 3-year pharmacy program, this is critical because the practice experiences occur concurrently with the didactic courses.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In their study conducted at a 4-year pharmacy program, Kidd and Latif found that PCAT composite score did not predict fourth-year experiential performance. 4 Our results suggest that additional admissions measures for experiential success are needed in order to ensure the students' overall academic success. In a 3-year pharmacy program, this is critical because the practice experiences occur concurrently with the didactic courses.…”
Section: Discussionmentioning
confidence: 82%
“…3 Other studies indicate the PCAT is a moderate to strong predictor of grades earned in pharmacy programs. [4][5][6] Other studies show that PCAT subtest scores are more predictive than the PCAT composite score of first-year GPA. [7][8][9] In addition to the PCAT, other predictors of academic success in the pharmacy programs are evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictors of academic success within pharmacy degree programs have included prepharmacy GPA and prepharmacy math/science GPA, 14,17,20,24 PCAT composite and PCAT subcategory scores, 18,20,21,25,27 and achievement of a 4-year college degree. 14,16,17,19,24,30 In contrast, some studies do not consider GPA as predictive, 14,16,18,19,23,27 some studies suggest use of the PCAT subcategory scores 10,15,20,22 over the PCAT composite score, and 1 study opposed the 4-year degree achievement as a predictor of success in pharmacy school. 22 Another study assessed factors related to advanced pharmacy practice experience (APPE) grades in doctor of pharmacy (PharmD) programs.…”
Section: Introductionmentioning
confidence: 99%